Methicillin-resistant Staphylococcus aureus prostatic abscess after traumatic rectal injury. Issue 3 (23rd March 2018) - Jarrah, Joud; Samji, Varun; Meshesha, Meron; Kothuru, Chandrasekhar; Al Hadidi, Samer
Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) commonly causes infection of the skin, soft tissue, bones and heart. MRSA is a rarely reported organism of prostatic abscess (PA). We present a case of an intravenous drug user who presented with dyspareunia, dysuria and dyschezia after a traumatic injury to the rectum. He was diagnosed with PA, which was treated with transurethral resection of the prostate drainage and intravenous antibiotics. MRSA PA carries a low case fatality rate on early diagnosis and treatment with proper antibiotics with or without drainage of the abscess.